Gifts Made During Death Illness Under Islamic Law - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2019)
Under the Islamic Law, property is regarded as a trust given by God to mankind to be used and expended in ways which are lawful and in accordance with the teachings of God. In his lifetime, a person has power to deal with his property as he deems fit. The only restraint upon a Muslim in the matter of alienating his property is that which relates to wills and death bed gifts. The validity of gifts is usually based on the saying of the Prophet (s.a.w) "send presents to each other for the increase of your love."